(untitled) (LEARNing Landscapes, 2023)
As educators, the need to adapt, change, and help students is always at the forefront. Today, there is a growing demand for teachers to innovate the curriculum to ensure accessibility and representation of student diversity as well as address inequities in education. This is an educator’s professional reflections on the relationship between innovation in education and the use of social justice in Quebec’s pedagogy, how to reduce injustices in the classrooms, and why it is necessary.